2020
DOI: 10.1055/s-0039-3402456
|View full text |Cite
|
Sign up to set email alerts
|

Predisposição familiar para rotura do manguito rotador e outras tendinopatias – Um estudo de caso-controle

Abstract: Familiares que realizaram tratamento para rotura do manguito rotador Sim 23 (31,9%) 9 (12,5%) 0,005 3,3 (1,4-7,7)Não 49 (68,1%) 63 (87,5%) Rev Bras OrtopPredisposição familiar para rotura do manguito rotador e outras tendinopatias Assunção et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…2 Genetic variations have been presented as intrinsic risk factors associated with the development of tendinopathy. 2,4,11,24 The gene-environment interaction of some modifiable risk factors, especially in athletes, related to the intensity and volume of training or competitions, and not modifiable, such as the genetic profile of the athlete, may result in a synergistic effect on the manifestation of tendon injury. 25 A systematic review study involving 17 studies on the influence of genes linked to collagen structure and tendon homeostasis observed the relevance of the contribution of polymorphisms in genes encoding collagen with susceptibility to Achilles tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Genetic variations have been presented as intrinsic risk factors associated with the development of tendinopathy. 2,4,11,24 The gene-environment interaction of some modifiable risk factors, especially in athletes, related to the intensity and volume of training or competitions, and not modifiable, such as the genetic profile of the athlete, may result in a synergistic effect on the manifestation of tendon injury. 25 A systematic review study involving 17 studies on the influence of genes linked to collagen structure and tendon homeostasis observed the relevance of the contribution of polymorphisms in genes encoding collagen with susceptibility to Achilles tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…2 Variações genéticas vêm sendo apresentadas como fatores de risco intrínsecos associados com o desenvolvimento da tendinopatia. 2,4,11,24 A interação gene-ambiente de alguns fatores de risco modificáveis, principalmente em atletas, relacionados a intensidade e volume de treinamentos ou competições, e não modificáveis, como o perfil genético do atleta, podem resultar em um efeito sinérgico na manifesta-ção da lesão no tendão. 25 Um estudo de revisão sistemática envolvendo 17 estudos sobre a influência de genes ligados à estrutura do colágeno e homeostase do tendão observou relevância da contribuição de polimorfismos nos genes que codificam o colágeno com a suscetibilidade à tendinopatia de Aquiles.…”
Section: Discussionunclassified